Особливості моделювання процесів радіально-поздовжнього видавлювання із використанням трикутних кінематичних модулів - Грудкіна, Н. С.; Hrudkina, N. S. (Кременчуцький національний університет імені Михайла Остроградського, 2020)
З метою дослідження вбудовуваності в загальні розрахункові схеми процесів послідовного радіальнопоздовжнього видавлювання запропоновано кінематичний модуль трикутної форми. Отримано величину приведеного тиску деформування всередині модуля із урахуванням верхньої оцінки за Коші-Буняковським потужності сил деформування, сил тертя на поверхні контакту інструменту та напівфабрикату та зрізу для суміжних модулів. Відхилення верхньої оцінки для величини повного приведеного тиску деформування загальної розрахункової схеми не перевищує 1–3%. З огляду на перспективність застосування даного кінематичного модуля у розрахунках процесів радіально-прямого видавлювання запропоновано у якості суміжних модулів обрати різновиди, що дозволять моделювати процеси із розвинутою складовою радіальної течії металу. Умови тертя та відносна величина товщини стінки, що видавлюється, суттєво впливають на оптимальне значення h , яке визначає оптимальну з точки зору зниження силових режимів конфігурацію інструменту. Одержану в результаті величину приведеного тиску рекомендовано використовувати в загальних розрахункових схемах радіальнопрямого видавлювання. Отримані результати сприятимуть визначенню оптимальної конфігурації інструмента та розробці відповідних технологічних рекомендацій.

Improving the technology of combined radial longitudinal extrusion processes based on the development of effective computational process modeling schemes by using economic models of a triangular shape. Methodology. Based on the prospects for the introduction of combined longitudinal-transverse extrusion processes in manufacturing, it is necessary to expand the capabilities of the energy method for modeling these processes with considering the complexity of the tool configuration and the boundaries of the flow inside the billet. To describe the complex nature of the metal flow during the transition from radial to forward extrusion, there is a need to develop triangular kinematic mod ules. To obtain the magnitude of the reduced pressure inside the kinematic module in an analytical form, it is necessary to use techniques to simplify the power of the deformation forces, friction forces, and shear. Comparative analysis in the magnitude of the reduced pressure with considering the deformation forces and the upper bound that was obtained by Cauchy-Bunyakovsky has confirmed the validity of this replacement. The deviation of the upper bound for the total reduced strain pressure of the general design scheme does not exceed 1-3%. This made it possible to obtain in analytical form the magnitude of the reduced pressure and to analyze the possibility of optimization by parameters characterizing the features of the tool configuration. Results. The value of the reduced pressure inside the module with considering the upper bound by Cauchy-Bunyakovsky and also power of the deformation forces, the friction forces on the contact surface of the tool and the semi-finished product and the shear for adjacent modules are considered. To use this kinematic module in the calculations of radial forward extrusion processes, it is proposed to choose as adjacent varieties that allow modeling processes with a developed radial metal flow. Friction conditions and extruded wall thickness, significantly affect the optimal value of the parameter, determining the optimal configuration of the tool in terms of reducing power modes. Originality. The resulting reduced pressure value is recommended to be used in general design schemes for radial forward extrusion. This will expand the capabilities in predicting the power modes of these processes with considering optimal configuration of the tool and their wider implementation in manufacturing. Practical. The results will contribute to determining the optimal configuration of the tool and the development of appropriate technological recommendations.
Features of modeling in radial-longitudinal extraction processes by using triangular kinematic modules
Keywords: радіально-поздовжнє видавлювання; математичне моделювання; приведений тиск деформування; radial longitudinal extrusion; mathematical modeling; reduced deformation pressure